Zapobieganie i zwalczanie handlu ludźmi przez Policję i Straż Graniczną na terytorium RP - Piontek, Łukasz (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2018)
The article aims to show issues related to the prevention and combating of human trafficking. Two formations are subjected to scientific reflection: the Border Guard and the Police, which, through their statutory tasks, independently and in cooperation with other entities, stand on the guard over the security of the Republic of Poland. Human trafficking is a global problem that also includes Poland. This article consists of several parts: definition of a crime of human trafficking, regulated in Polish criminal law, forms of human trafficking that occur on the territory of Poland, tasks and competences of the Police and the Border Guard in preventing and combating human trafficking, and statistical recognition of these two formations on the crime of human trafficking. The article, by attempting to analyze the presented issues, is an attempt to achieve the goal set by the author.